Epistaxis in Patients Receiving Oral Anticoagulants and Antiplatelet: Prevalence, Risk Factors at a Tertiary Care Hospital in Nepal: A Cross‐Sectional Study - Shiv Kumar Sah; Ashok Kumar Gupta; Sanjaya Acharya; Suraj Kumar Thakur; Rajkumar Chaudhary; Shiva Pandeya; Arjun Budthapa; Vijaya K. C.; Sajish Khadgi; Manjita Bajracharya (Health Science Reports, 2026)
ABSTRACT Background and Aims Epistaxis is a common complication associated with oral anticoagulant and antiplatelet therapies, often leading to significant morbidity. In recent years, the incidence of cardiovascular disease in Nepal has risen dramatically, driving a widespread use of these medications and heightened concerns regarding bleeding complications. Despite this growing concern, epidemiological data on epistaxis in the Nepalese population is rarely documented. This study aims to determine the prevalence of epistaxis and identify the associated risk factors among patients receiving oral anticoagulants and antiplatelets at a tertiary care hospital in Nepal. Methods A cross‐sectional study was conducted among 284 patients receiving oral anticoagulants at a tertiary care hospital over a 1‐year period. Data were collected through structured interviews and medical record reviews. The prevalence of epistaxis with corresponding 95% CI was calculated, and risk factors were analyzed using multivariate logistic regression. A receiver operating characteristic (ROC) curve was determined to establish the suitability of the model. Results Of the 284 patients, 23.2% (95% CI: 18.4%–28.5%) experienced epistaxis, with 23.2% (95% CI: 18.4%–28.5%) of cases classified as moderate in severity. In multivariate model, age (as continuous) (AOR: 1.068; 95% CI: 1.009–1.13), age (category) ≥ 60 years (AOR: 6.21; 95% CI: 1.20–32.16), male gender (AOR: 1.87; 95% CI: 1.032–3.41), rural residency (AOR: 1.96; 95% CI: 1.04–3.71), having Congestive heart failure (AOR: 2.38; 95% CI: 1.012–5.62), being hypertensive (AOR: 3.14; 95% CI: 1.50–6.53), and individuals on warfarin therapy (AOR: 3.14; 95% CI: 1.50–6.53) emerged as independent predictors associated with the increased risk for experiencing epistaxis. The model revealed a good applicability (AUC: 0.71; 95% CI: 0.64–0.78). Conclusion Epistaxis remained a common complication among patients receiving oral anticoagulant therapy in Nepal, with advancing age, male gender, rural residency, hypertension, congestive heart failure, and warfarin therapy identified as significant risk factors. These findings underscore the need for enhanced patient monitoring and tailored care plans to mitigate bleeding risks in high‐risk groups.